2018
DOI: 10.1038/s41598-018-31724-8
|View full text |Cite
|
Sign up to set email alerts
|

The quaternary structure of Thermus thermophilus aldehyde dehydrogenase is stabilized by an evolutionary distinct C-terminal arm extension

Abstract: Aldehyde dehydrogenases (ALDH) form a superfamily of dimeric or tetrameric enzymes that catalyze the oxidation of a broad range of aldehydes into their corresponding carboxylic acids with the concomitant reduction of the cofactor NAD(P) into NAD(P)H. Despite their varied polypeptide chain length and oligomerisation states, ALDHs possess a conserved architecture of three domains: the catalytic domain, NAD(P)+ binding domain, and the oligomerization domain. Here, we describe the structure and function of the ALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 62 publications
1
35
0
Order By: Relevance
“…However, emerging research suggests the contrary. The novel ALDH from T. thermophilus HB27 (TtALDH 530 ) Hayes et al (2018) showed an interesting feature with an unusual extended C-terminal tail compared to available structures (Figure 7). In contrast to other ALDHs, this extended tail contributes to the tetrameric assembly and the stability of the protein as it completely wraps the opposing monomer.…”
Section: Nad(p) Cofactor Choice and Utilisationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, emerging research suggests the contrary. The novel ALDH from T. thermophilus HB27 (TtALDH 530 ) Hayes et al (2018) showed an interesting feature with an unusual extended C-terminal tail compared to available structures (Figure 7). In contrast to other ALDHs, this extended tail contributes to the tetrameric assembly and the stability of the protein as it completely wraps the opposing monomer.…”
Section: Nad(p) Cofactor Choice and Utilisationmentioning
confidence: 99%
“…To date 10 out of the 19 human ALDHs have a resolved structure. Initially this led to misconceptions and a rather inaccurate description of typical features related to the enzyme family (Rodríguez-Zavala et al, 2006;Hayes et al, 2018). Emerging research allows for an accurate understanding of diversity within the ALDH family, across prokaryotes and eukaryotes, while bridging the gap to form a global perception of the superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…While ALDHs have been well-characterised in humans, emerging research places a primary focus on their prokaryotic counterpart’s structure and function, which has been less explored until recently [ 29 , 30 , 31 ]. The scope of prokaryotic ALDH function spans much wider than eukaryotes [ 5 , 19 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The metabolite nicotinamide adenine dinucleotide (NAD + ) plays a key role in major metabolic pathways including glycolysis, tricarboxylic acid (TCA) cycle, and oxidative phosphorylation (19). Furthermore, NAD + is a co-factor for ALDH enzymes and essential for the ALDH-mediated conversion of aldehydes to carboxylic acids (20,21). Ovarian tumors with reduced expression of BRCA1 through BRCA1 promoter DNA hypermethylation or mutation have increased levels of NAD + and expression of nicotinamide phosphoribosyltranferase (NAMPT), the rate limiting regulator of NAD + synthesis from the salvage pathway (22).…”
Section: Introductionmentioning
confidence: 99%